Mechanisms by which synthetic 6,7-annulated-4-substituted indole compounds with anti-proliferative activity disrupt mitosis and block cytokinesis in human HL-60 tumor cells in vitro - Perchellet, Jean-Pierre H.; Perchellet, Elisabeth M.; Singh, Chingakham R.; Monnett, Meghan T.; Studer, Elizabeth R.; Thornton, Paul D.; Brown, Neil; Hill, David; Neuenswander, Ben; Lushington, Gerald H.; Santini, Conrad; Buszek, Keith R. (My University, 2014)
Background: Synthetic 6,7-annulated-4-substituted indole compounds, which elicit interesting antitumor effects in murine L1210 leukemia cells, were tested for their ability to inhibit human HL-60 tumor cell proliferation, disrupt mitosis and cytokinesis, and interfere with tubulin and actin polymerization in vitro. Materials and Methods: Various markers of metabolic activity, mitotic disruption and cytokinesis were used to assess the effectiveness of the drugs in the HL-60 tumor cell system. The ability of annulated indoles to alter the polymerizations of purified tubulin and actin were monitored in cell-free assays and were compared to the effects of drugs known to disrupt the dynamic structures of the mitotic spindle and cleavage furrow. Results: With one exception, annulated indoles inhibited the metabolic activity of HL-60 tumor cells in the low-micromolar range after two and four days in culture but these anti-proliferative effects were weaker than those of jasplakinolide, a known actin binder that blocks cytokinesis. After 24-48 h, antiproliferative concentrations of annulated indoles increased the mitotic index of HL-60 cells similarly to vincristine and stimulated the formation of many bi-nucleated cells, multi-nucleated cells and micronuclei, similarly to taxol and jasplakinolide, suggesting that these antitumor compounds might increase mitotic abnormality, induce chromosomal damage or missegregation, and block cytokinesis. Since annulated indoles mimicked the effect of vincristine on tubulin polymerization, but not that of taxol, these compounds might represent a new class of microtubule de-stabilizing agents that inhibit tubulin polymerization. Moreover, annulated indoles remarkably increased the rate and level of actin polymerization similarly to jasplakinolide, suggesting that they might also stabilize the cleavage furrow to block cytokinesis. Conclusion: Although novel derivatives with different substitutions must be synthesized to elucidate structure–activity relationships, identify more potent antitumor compounds and investigate different molecular targets, annulated indoles appear to interact with both tubulin to reduce microtubule assembly and actin to block cytokinesis, thereby inducing bi- and multinucleation, resulting in genomic instability and apoptosis.
Keywords: Annulated indoles; Tumor cell proliferation; Cells with mitotic figures; Several nuclei and micronuclei; Cytokinesis; Tubulin polymerization; Actin polymerization